Academic cheating, achievement orientations, and culture values: A Meta-Analysis - Zhao, Li; Yang, Xinchen; Yu, Xinyi; Zheng, Jiaxin; Mao, Haiying; Fu, Genyue; Fang, Fang; Lee, Kang (Review of educational research, 2024)
This preregistered meta-analysis investigated whether cultural values moderate the relations between students’ achievement orientations and their tendency to cheat. We identified 80 studies on the associations between performance/learning orientations and academic cheating in 27 countries with 40,867 participants. Performance orientation positively correlates with academic cheating (r = .09, 95% CI = 0.04 to 0.13), and learning orientation negatively correlates with academic cheating (r = −.16, 95% CI = −0.20 to -0.13). Univariate meta-analysis, hierarchical meta-regression, and meta-analytic structural equation modeling (MASEM) revealed that cultural values at the country level significantly moderate the relations between achievement orientations and cheating. These findings suggested that cultural values play a significant role in influencing the relations between achievement orientations and academic cheating, and, thus, cheating prevention programs must consider culture to achieve optimal effects. Based on these findings, we propose a new model that integrates cultural values into the existing model of academic cheating decision-making.
Online veröffentlicht: 13. November 2024
Gesehen am 26.06.2025